Health professional students’ perceptions and preparedness for interprofessional education: a multicentric analysis across five countries - Alsharari, Thani; Khattak, Osama; Agarwal, Anshoo; Chaudhary, Farooq Ahmad; Suhail, Nida; Begum, Gulam Saidunnisa; Subramaniam, Geetha; Albagami, Hathal; Felemban, Mohammed Fareed; Shawli, Hassan Talat; Algahtani, Fahad Saeed; Fareed, Muhammad Amber (Frontiers in Medicine, 2025)
IntroductionInterprofessional education (IPE) prepares health professional students for teamwork in clinical practice. The success of IPE depends on students’ readiness and acceptance of interprofessional learning. This study aimed to assess the perceptions and readiness for IPE among health professional students across universities in five countries, using the Readiness for Interprofessional Learning Scale (RIPLS).MethodsA cross-sectional descriptive study was conducted among 335 students from health professional programs at universities in Saudi Arabia, Malaysia, Nepal, India, and Pakistan. The Readiness for Interprofessional Learning Scale (RIPLS) questionnaire was used to collect data prior to any structured workshop activities, and results represent baseline perceptions of IPE. Responses were analyzed using descriptive statistics, paired-samples t-tests, and analysis of variance (ANOVA) to compare groups.ResultsThe study found significant differences (p < 0.001) in IPE readiness between students from different countries and academic years. Students from Malaysia, India, and Pakistan demonstrated higher readiness for IPE, with senior students showing greater readiness compared to juniors. The mean readiness score for teamwork and collaboration was 4.2 (SD = 0.7) in Malaysia, while students in Nepal had the lowest mean score of 3.2 (SD = 1.5). Overall, senior students exhibited higher readiness for teamwork and collaboration (mean = 4.3, SD = 0.4) compared to first-year students (mean = 3.6, SD = 1.9).ConclusionThe findings underscore the need for targeted IPE initiatives that are adapted to different academic levels and contexts. Integrating IPE early in healthcare curricula is critical for enhancing collaborative skills and improving patient outcomes. These results have important implications for curriculum developers and policymakers aiming to foster interprofessional collaboration in healthcare education.